2015
DOI: 10.1002/pmj.21478
|View full text |Cite
|
Sign up to set email alerts
|

Communication Behaviors to Implement Innovations: How Do AEC Teams Communicate in IPD Projects?

Abstract: Implementing any innovation successfully is a challenge. In addition to commonly reported climate and values‐fit constructs, this study proposes that communication behaviors (i.e., monitoring, challenging, managing, and negotiating) are also vital for innovation implementation. Via an in‐depth literature review, the study first defines these metrics. Second, a content analysis of an integrated project delivery (IPD) case study report enables the study to explore if these communication behaviors exist in inter‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 37 publications
(82 reference statements)
1
23
0
Order By: Relevance
“…The study was followed up with a summarising of factors that influence collaboration in IPD teams (Zhang et al, 2013). Sun et al (2015) identified how communication behaviours in inter-organisational teams affect innovation. Paolillo et al (2016) explored the procedural and social elements of a large commercial construction project utilising people-centred innovation (PCI).…”
Section: Integrated Project Deliverymentioning
confidence: 99%
“…The study was followed up with a summarising of factors that influence collaboration in IPD teams (Zhang et al, 2013). Sun et al (2015) identified how communication behaviours in inter-organisational teams affect innovation. Paolillo et al (2016) explored the procedural and social elements of a large commercial construction project utilising people-centred innovation (PCI).…”
Section: Integrated Project Deliverymentioning
confidence: 99%
“…Pfeffermann (2011) viewed innovation communication as an integrative management capability, which is significant in the competitive economy because it “enables systematically planned transactional information transmissions related to innovations, context-issues of innovations and innovative capability” (p. 257) within a chosen strategy. Considering the risk and complexity of innovation and the resulting resistance within organizational adoption units, the literature has explored and explicated communication at the inception and operation stages of innovation, most of which is intraorganizational (Ebadi & Utterback, 1984; Monge et al, 1992; Ray et al, 1996), and even intragroup communication within the innovation team (Danowski, 1980; Fidler & Johnson, 1984; Kratzer et al, 2004; Moenaert et al, 2000; Sun et al, 2015). Findings have shown that in for-profit sectors, internal communication has a more positive influence on innovation than does external communication (Suh et al, 2018).…”
Section: Innovation Communication and Product Launch Presentationsmentioning
confidence: 99%
“…Previous studies have indicated that different forms of contracting parties' communication behaviors among contracting parties, including monitoring, challenging, managing, and negotiating, are vital for successful IPD implementation (Sun et al, 2015). This means social interactions can help facilitate collective practices and create a mutually beneficial atmosphere where project participants are willing to share knowledge and fully exert their advantages (Harpham et al, 2002).…”
Section: The Mediating Effect Of Social Capitalmentioning
confidence: 99%